P110 Establishing a pleural nurse service. (12th November 2019) - LeBon, A; Hallifax, RJ; Nicholson, T; Curry, L; Park, J
Abstract : Introduction: In 2016 a retrospective review of pleural procedures was undertaken to identify possible areas for improvement. In 2017, funding was approved for a nurse-led pleural service and appointed to in December 2017. Following an initial training period, the pleural nurse has been an independent practitioner since August 2018. We report key performance indicators from 2018 and the first 6 months of 2019. Methods: Pleural procedural contacts and activity were prospectively collected from January 2018 and compared to data from 2016. Records of number and source of referrals, type of procedure and indication were reviewed. In addition, patients were surveyed to collect feedback on their experience of the service. Results: Pleural activity has been demonstrated to have increased this year; 241 to June 2019; 278 in 2018 and 287 in 2016. At least 52 admissions were avoided as a result of acute referrals being managed on pleural lists as an outpatient during 2018 and the first 6 months of 2019. A higher proportion of procedures were performed as a daycase in 2018 (42% vs 25%). Pleural nurse activity increased throughout 2018, including pleural procedures, inpatient ward reviews, telephone advice and follow-up (Figure 1). We have doubled the amount of junior doctor training opportunities and are providing more day case IPC insertions in 2019. Fewer consultant hours were required to deliver the service. Patient feedback has been positive, with 100% of patients surveyed knowing the correct person to contact with queries, improved from an initial 25%. Discussion: The development of the pleural nurse role has successfully streamlined the service as a single point of contact for referrals and patients. This has led to increased outpatient work, saved admissions to hospital and saved consultant time; thereby delivering cost savings to the trust. Pleural activity has increased in the first 6 months of this year; this reflects a genuine increase in procedural work in addition to improved data capture and coding. More importantly, the patient experience of our service has improved.